Special issue: "Ethical questions in transforming music practices" - Kivijärvi, Sanna; Koivisto, Taru-Anneli (Queen Margaret University, 2025)
The themes of equity and justice in professional activities are becoming increasingly important for those working in music-related fields. This special issue explores these topics through the lens of ethical dilemmas and challenges, drawing on international perspectives from scholars and practitioners. Ethical decision-making requires professionals not only to engage in critical thinking and self-reflection but also to take action by transforming organisational and institutional structures. --
Keywords: musiikki; etiikka; musiikkiterapia